2015
DOI: 10.1515/popore-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and screening of Actinobacteria in volcanic soil of Deception Island (the Antarctic) for antimicrobial metabolites

Abstract: This project aimed to isolate and characterize volcanic soil Actinobacteria from Deception Island, Antarctic. A total of twenty−four Actinobacteria strains were isolated using four different isolation media (Starch casein agar, R2 agar, Actinomycete isolation agar, Streptomyces agar) and characterized basing on 16S rRNA gene sequences. Tests for second− ary metabolites were performed using well diffusion method to detect antimicrobial activities against eight different pathogens, namely Staphyloccocus aureus A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These findings confirm the abundant bacterial diversity in Antarctic environments. Comparably, Gordonia terrae , Leifsonia soli , and Terrabacter lapilli isolated from Antarctic volcanic soils showed inhibitory activity against S. enterica serotype Paratyphi and S. enterica serotype Enteritidis [58]. Other marine Actinobacteria have been reported to have antimicrobial activity against numerous human pathogens.…”
Section: Antarctic Exhibits Significant Diversity Of Antibiotic-prmentioning
confidence: 99%
“…These findings confirm the abundant bacterial diversity in Antarctic environments. Comparably, Gordonia terrae , Leifsonia soli , and Terrabacter lapilli isolated from Antarctic volcanic soils showed inhibitory activity against S. enterica serotype Paratyphi and S. enterica serotype Enteritidis [58]. Other marine Actinobacteria have been reported to have antimicrobial activity against numerous human pathogens.…”
Section: Antarctic Exhibits Significant Diversity Of Antibiotic-prmentioning
confidence: 99%
“…Streptomycetes are complex filamentous Gram-positive bacteria with morphology resembles those of fungi 1113 . The complexity of streptomycetes can be observed through their complicated developmental life cycle and their large genome size of more than 8 Mbp with high G + C content,often associated with their ability to prosper and survive in different environments 1316 . Studies also revealed the presence of over 20 biosynthetic gene clusters related to biosynthesis of secondary metabolites in the large genome of streptomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…The phylum Actinobacteria signify a significant constituent of the microbial population in most soils [134][135][136][137][138] ; such as the Antarctic region [117][118][119]139] . Also, Actinobacteria present in rhizosphere soil were reported for discovery of antimicrobial agents and other useful metabolites [140][141][142][143][144][145][146][147][148][149][150][151] . The genus Streptomyces exhibited potential as bio-control agent of commercial crops against fungal pathogens [17,152] .…”
Section: Bacteria As Source Of New Natural Productsmentioning
confidence: 99%